Diagnostic reliability of pediatric appendicitis score, ultrasound and low-dose computed tomography scan in children with suspected acute appendicitis - Sayed, Ashraf Othman (Ther Clin Risk Manag, 2017)
BACKGROUND: Diagnosis of appendicitis in children is clinically challenging. Computed tomography (CT) is the gold standard for diagnosis; however, radiation exposure early in life is a concern with this technique. Therefore, in this study, we aimed to evaluate the diagnostic reliability of low-dose CT, pediatric appendicitis score (PAS), and abdominal ultrasound (US) in children with acute appendicitis, to reach a safe diagnosis. PATIENTS AND METHODS: This retrospective study was conducted on 140 children who were admitted with clinically suspected acute appendicitis (45 with positive appendicitis and 95 children with negative appendicitis). Low-dose CT was performed, and PAS was retrospectively calculated for all subjects. US was initially performed for 38 subjects. All results were compared with the final diagnosis reached by an operative, histopathological analysis and follow-up. RESULTS: Low-dose CT showed a sensitivity, specificity, and accuracy of 97.8%, 100%, and 99.3%, respectively. At a cutoff value ≥5, PAS showed a sensitivity, specificity, and accuracy of 95%, 84%, and 89%, respectively. Abdominal US examination showed sensitivity, specificity, and accuracy of 55.6%, 85%, and 71%, respectively. Implementing Poortman’s model resulted in higher accuracy (92%) of US. There was a significant difference in accuracy between a low-dose CT and PAS on one side and between Poortman’s model and US examination on the other side. A diagnostic scheme was suggested using PAS as the excluding tool (PAS ≤2 send home and ≥7 send directly to operation) followed by US examination and reserving low-dose CT for inconclusive cases. This scheme would eliminate the use of CT for at least 33.7% and in 7 cases who had initial US examination. CONCLUSION: Although CT remains the most accurate and less operator-dependent diagnostic tool for pediatric appendicitis, the radiation hazards could however be minimized using PAS as an excluding tool and US as the primary imaging modality followed by low-dose CT for inconclusive cases only.